P redicting PIeU patient survival prognosis: Pediatric Logistic Organ Dysfunction vs Pediatric Index of Mortality scores - Edwina Winiarti; Muhammad Sholeh Kosim; Mohammad Supriatna (Indonesian Pediatric Society Publishing House, 2012)
Background Determining prognosis of patients using scoring systems have been done in many pediatric intensive care units (PIeU). The scoring systems frequently used are pediatric logistic organ dy sfunction (PELOD), pediatric index of mortality (PIM) and pediatric risk of mortality (PRISM). Objective To compare the performance of PELOD and PIM scores in predicting the prognosis of survival vs death in PIeU patients. Methods A prognostic test in this prospective, cohort study was conducted in the PIeu of the Kariadi General Hospital, Semarang. PELOD and PIM calculations were performed using formulae from previously published articles. Statistical analyses included receiver operating curve (ROC) characteristics to describe discrimination capacity, sensitivity, specificity, positive predictive value, negative predictive value and accuracy. Results Thirty􀁊three patients fulfilling the inclusion criteria were enrolled in the study. PELOD score for area under the ROC was 0.87 (95% CI 0.73 to 1.0; P􀁋0.003), while that for PIM was 0.65 (95% CI 0.39 to 0.90; P􀁋0.2). PELOD scores showed sensitivity 85.7% (95% CI 59.8 to 100), specificity 84.6% (95% CI 70.7 to 98.5), positive predictive value 60.0% (95% CI 29.6 to 90.4)' negative predictive value 95.6% (95% CI 87.3 to 100) and accuracy 84.8%. PIM scores showed sensitivity 85.7% (95% CI 59.8 to 100), specificity 50.0% (95% CI 30.8 to 69.2), positive predictive value 31.6% (95% CI 10,7 to 52.5), negative predictive value 92.9% (95% CI 79.4 to 100) and accuracy 57.6%. Conclusion PELOD scoring had better specificity, positive predictive value, negative predictive value, accuracy and discrimination capacity than PIM scoring for predicting the survival prognosis of patients in the PICU. [Paecliatr Inclanes. 2012;52:165-9].